Assessment of Health Promotion Based on “PHBS” Marketplace Indicators in Kediri Regency - Yudhi Ahmad Zarnuzi (Universitas Airlangga, 2020)
Background: Traditional markets are a place to fulfill basic daily needs with trading practices accompanied by direct interaction between sellers and buyers. Health promotion in public places needs to be carried out by providing facilities that can support healthy behavior for visitors. One of the effort is through the indicators of Clean and Healthy Behavior. Objective: This research aims to explore and seek appropriate recommendations so that it can be a reference in improving clean and healthy living in the traditional market environment. Method: The instruments used in this study were the field observation form, assessment form, and in-depth interview guide. Taking informants using purposive sampling techniques with inclusion criteria is the market manager. The assessment was carried out on the components of a Healthy Clean Lifestyle in traditional markets, namely 8 indicators including clean water supply, hand washing behavior with soap, healthy latrines, behavior to dispose of rubbish in its place, not smoking in public places, closing food and drinks, prohibiting indiscriminate spitting, and efforts to eradicate mosquito larvae. Results: The results of this study indicate that the four markets studied were in the Poor category. The Main Market gained 447 points, the Pamenang Market 350 points, the Pare Lama Market 352 points, the Bendo Market 366 points. There are four indicators that have the results with the lowest achievement score, namely indiscriminate spitting, smoking bans in public places, washing hands with soap, and combating mosquito larvae. Conclusion: several Traditional Markets in Pare Sub-district have not implemented 8 Indicators of Clean and Healthy Behavior in public places (Traditional Markets) properly.